A parametric study on the modified slenderness ratio for cold-formed steel built-up back-to back channel stub column - Lau, H.; Ting, T.C.H. (Southern University Press, 2012)
Built-up member design is addressed in provision C4.5 of the American Iron and Steel Institute 2001 Specification (AISI). A finite elements model of the built-up member was created for this parametric study on the slenderness ratio formulae of the provision C4.5 in AISI design specification. The governing slenderness ratio of built-up member in the AISI design specification is that a/r does not exceed half of the governing slenderness ratio of the overall built-up member. This study examined the 0.5 requirement for this governing slenderness ratio of the built-up member with or without the use of the modified slenderness ratio of the provision C4.5. The parametric study focused on built-up columns composed of two channels connected back-to-back at their webs. This study was performed on stub columns with different material thicknesses and connector spacing. Comparison of the finite element and theoretical results concluded that the use of the modified slenderness equations of provision C4.5 will give a more conservative capacity prediction when the spacing, s between the connectors along the length of the specimen increased. Also, with thicker material thickness, the modified slenderness ratio also will give a more conservative capacity prediction.